Disability in the Christian tradition : a reader - Brock, Brian, 1970-; Swinton, John, 1957- (Grand Rapids, Mich. : W.B. Eerdmans Pub. Co., 2012)
This book brings together for the first time the views of renowned Christian leaders throughout history - including Augustine, Aquinas, Julian of Norwich, Luther, Calvin, Hegel, Kierkegaard, van den Bergh, Bonhoeffer, Barth, Vanier, and Hauerwas. Fourteen experts in theology and disability studies guide readers through each era or group of thinkers, offering clear commentary and highlighting important themes. --from publisher description.
Introduction: Disability and the quest for the human / Brian Brock -- The patristic era : early Christian attitudes toward the disfigured outcast / Almut Caspary -- Augustine's hierarchies of human wholeness and their healing / Brian Brock -- Aquinas on the corporis infirmitas : broken flesh and the grammar of grace / Miguel J. Romero -- A ravishing the restful sight : seeing with Julian of Norwich / Amy Laura Hall -- The human condition as seen from the cross : Luther and disability / Stefan Heuser -- John Calvin and disability / Deborah Beth Creamer -- To develop relational autonomy : on Hegel's view of people with disabilities / Martin Wendte -- Between necessity and possibility : Kierkegaard and the abilities and disabilities of subjectivity / Christopher Craig Brittain -- People are born from people : Willem Van den Bergh on mentally disabled people / Marjolein de Mooij -- "My strength is made perfect in weakness" : Bonhoeffer and the war over disabled life / Bernd Wannenwetsch -- This ability : Barth on the concrete freedom of human life / Donald Wood -- Women, disabled / Jana Bennett -- Being with the disabled : Jean Vanier's theological realism / Hans S. Reinders -- The importance of being a creature : Stanley Hauerwas on disability / John Swinton.
Includes bibliographical references and indexes.
Print version record.
English.
Master record variable field(s) change: 650
Keywords: Disabilities -- Religious aspects -- Christianity; Theological anthropology -- Christianity; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; People with disabilities -- Religious aspects -- Christianity; Theological anthropology -- Christianity; Electronic books